2010
DOI: 10.1021/ja909962f
|View full text |Cite
|
Sign up to set email alerts
|

Base-Induced Mechanistic Variation in Palladium-Catalyzed Carbonylation of Aryl Iodides

Abstract: A mechanism, which is distinct from the traditional one when sodium alkoxide was used instead of tertiary amines, was proposed for the alkoxycarbonylation of aryl iodides. The catalytic cycle was composed of oxidative addition, subsequent ArPdOR formation, CO insertion to Pd-OR, and final reductive elimination of ArPdCOOR. The kinetic simultaneity of the formation of deiodinated side product from the aryl iodide and aldehyde from corresponding alcohol provided strong evidence for the existence of ArPdOR specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 41 publications
4
69
0
Order By: Relevance
“…The kinetic profiles were overlaid, indicating that the insertion of CO was not rate-determining under the conditions. On the basis of above results and previous studies, [10] we propose a mechanism for this double C À H functionalization/ carbonylation reaction (Scheme 2). On the basis of above results and previous studies, [10] we propose a mechanism for this double C À H functionalization/ carbonylation reaction (Scheme 2).…”
supporting
confidence: 65%
“…The kinetic profiles were overlaid, indicating that the insertion of CO was not rate-determining under the conditions. On the basis of above results and previous studies, [10] we propose a mechanism for this double C À H functionalization/ carbonylation reaction (Scheme 2). On the basis of above results and previous studies, [10] we propose a mechanism for this double C À H functionalization/ carbonylation reaction (Scheme 2).…”
supporting
confidence: 65%
“…[2] Notable examples include native chemical ligation (NCL) for peptidea nd protein synthesis as well as amideand ester formation. [2b] Significant advances on developing atom-economical catalytic methodsh ave been made, [2c] typicallyc arried out with transition metals as catalysts such as carbonylation, [4] cross-coupling [5] and allylic substitution. [2b] Significant advances on developing atom-economical catalytic methodsh ave been made, [2c] typicallyc arried out with transition metals as catalysts such as carbonylation, [4] cross-coupling [5] and allylic substitution.…”
mentioning
confidence: 99%
“…[15] Nonetheless, they mediated HATg enerally carried out under UV light. [4,11,12] Our exploratory studies began with am odel reaction of aldehyde 1a (0.2 mmol) with commonlyu sed sulfenyl donors (0.24 mmol) including thiol, disulfide and thiosulfonate S-ester 2a in the presence of ak etone catalyst( 0.01 mmol) in MeCN (2.0 mL) irradiated with blue LEDs under N 2 atmosphere (Table 1). [16] Studies have shown that bond dissociation enthalpy (BDE) considerations are less important than CÀHb ond polarity in HAT.…”
mentioning
confidence: 99%
“…A similar catalytic cycle based on kinetic studies to account for the alkoxycarbonylation of aryl iodides in the presence of sodium alkoxides has been previously postulated; however, this sequence is less likely in absence of strong bases 22. Formation of intermediate ArS(O)CH 2 PdOR via metathesis from the oxidative addition complex, followed by insertion of carbon monoxide into the Pd-OR bond and, finally, reductive elimination, cannot be ruled out to explain the alkoxycarbonylation reaction.…”
mentioning
confidence: 81%